2002
DOI: 10.1149/1.1449953
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Constraints on High Aspect Ratio Silicon Microstructures Fabricated by HF Photoelectrochemical Etching

Abstract: The fabrication of macropores in crystalline silicon by photoelectrochemical etching in a hydrofluoric acid electrolyte is investigated. It is shown that the dimensional constraints on the pore diameters, which, in previous literature, are considered to depend on substrate doping, can be significantly relaxed. We show that it is possible to fabricate arrays of square section macropores with sides ranging from 2 to 15 m using the same n-doped ͑2.4-4 ⍀ cm͒ silicon substrate. Moreover, we demonstrate that macropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 15 publications
2
23
2
2
Order By: Relevance
“…[9] regular pores with sides ranging from 2 µm up to 15 µm and pitch variation up to 100% were fabricated on the same 2.4÷4 Ω·cm silicon substrate. Moreover, we showed that macropore formation is just a feature of photo-electrochemical etching and that by changing the initial pattern it is possible to fabricate a variety of silicon microstructures with more complicated shape [8]. As a matter of fact, fabrication of regular arrays of walls, tubes, spirals, pillars was demonstrated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[9] regular pores with sides ranging from 2 µm up to 15 µm and pitch variation up to 100% were fabricated on the same 2.4÷4 Ω·cm silicon substrate. Moreover, we showed that macropore formation is just a feature of photo-electrochemical etching and that by changing the initial pattern it is possible to fabricate a variety of silicon microstructures with more complicated shape [8]. As a matter of fact, fabrication of regular arrays of walls, tubes, spirals, pillars was demonstrated.…”
Section: Resultsmentioning
confidence: 97%
“…Applications of such structures to IR filters [5], photonic crystals [6] and micromechanical systems [7] have been reported as well. However, it was only very recently that photo-electrochemical etching has been verified as a tool for bulk silicon micromachining [8]. As a matter of fact, in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of optical characteristics of such photonic crystals showed that they can be successfully used in the mid IR region of the spectrum [2,3]. Later, simi lar structures were obtained using photoelectrochemi cal etching (PECE) of silicon with (100) orientation [4][5][6][7]; previously, this method had been mainly used to obtain a 2D periodic lattice in macroporous silicon [8][9][10]. The advantages of the PECE method as com pared to anisotropic etching consist in the use of a sub strate with the standard (100) orientation, in the absence of a necessity to precisely orient the pattern of the photomask with respect to crystallographic axes, and the possibility of fabricating simultaneously the trenches and macropores in a unified process [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[39] The shapes of these structures can either be defined by the shape of a physical object that is brought in close proximity of the substrate, or by using a masking layer, which can be deposited by various methods. [39,40] Using this technique, many complex shapes have been created, when the proper masking steps were used. [41,42] For example, in an comprehensive study on electrochemical etching, Bassu et al were able to fabricate a MEMS device, with high-aspect ratio (100) comb fingers suspended by high-aspect ratio folded springs.…”
Section: Wet Etchingmentioning
confidence: 99%